The Wages of Destruction - Adam Tooze (Journal of Economic Sociology, 2018)
The majority of accounts of the Second World War have described Nazi Germany as an uncontrollable monster with a highly industrialized economy. But what if it was not so? What if the European tragedy was not rooted in Germany’s strength, but in its weakness?Adam Tooze has written a radically new history of the Second World War. The author achieved this by taking into account racial relations and politics, with special attention focused on economy. Understanding of the global economy played a critical role in Hitler’s views. He guessed that Germany’s relative poverty in 1933 was conditioned by not only the Great Depression but also limitations of its territory and natural resources. He foresaw a rise of a new globalized world where Europe would be pressed by the unbreakable power of America. There was a last chance: the European superstate led by Germany. However, the global balance of economic and military forces did not initially favor of Hitler. With the purpose of preventing the threat from the West, he sent his poorly armed troops to conquer Europe which led to the crash of his intentions. Even in the summer of 1940, a time of Germany’s great triumphs, Hitler was worried about America’s air and maritime domination, which he was convinced was the result of a Jewish conspiracy. As soon as the Wehrmacht came into Soviet territory, the war turned into a battle of attrition without any hope of Germany’s winning. Because Hitler and others did not accept this, the Third Reich was destroyed at the cost of millions of lives. The Journal of Economic Sociology publishes the “Introduction” to this book.